PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN BIAYA CSR TERHADAP KINERJA PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2013-2017) - FRANSISCA DWI, ASTRIED; HANDAYANI, SUSI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to examine the effect of CSR disclosure and CSR costs on company performance. This study uses company size and company age as control variables. The research sample was selected using the purposive sampling method, so that a sample of 35 manufacturing companies was listed on the Indonesia Stock Exchange during the 2013-2017 period. Data collection techniques used this study are documentation and content analysis. The data analysis technique used in this study is multiple regression analysis with moderation regression by using SPSS verion 23 software. The results of the study show that the disclosure of CSR affects the performance of the company. CSR costs have an influence on company performance. Company size as a control variable influences company performance. The age of the company influences the companys performance.Keywords : Corporate Social Responsibility, CSR Costs, and Company Performance